Reproductive pattern of Trochita pileolus (d' Orbigny, 1841) (Gastropoda: Calyptraeidae) and different types of intracapsular development in Trochita species of South America - Penchaszadeh, Pablo; Arrighetti, Florencia; Aldea Venegas, Cristian Leonardo; Teso, Valeria (My University, 2022)
Several types of development are reported in the worldwide distributed Family Calyptraeidae. In species with direct development, embryos can grow from large eggs or can feed on nurse eggs, nurse embryos, or other intracapsular nutritional resources. Here the reproductive mode of Trochita pileolus and how biochemical composition varies among egg size between three species of Trochita were studied. Adults and broods of T. pileolus were collected off Tierra del Fuego and nearby Burdwood Bank at depths of 96-151 m. The mean shell diameter of brooding females was 16.3 +/- 2 mm and the number of egg capsules observed ranged from 5 to 9. In each egg capsule 7-10 embryos developed from uncleaved eggs of about 500 mu m diameter. Neither nurse eggs nor other kinds of extraviteline food sources were recorded. No oophagy, adelphophagy, or late intracapsular cannibalism were observed. The development mode of T. pileolus closely resembles that of the giant T. trochiformis from Chile, in which the energy for developing embryos is obtained from large fertile eggs. The eggs of T. trochiformis had higher lipid content than the other two species and were more energy-dense than glycogen-enriched eggs. The relative lipid coverage area and the hatching size of T. pileus were similar to T. pileolus, although the egg size was three times smaller. This could be attained because T. pileus has developed intracapsular nutritional resources such as nurse eggs and adelphophagy.
Keywords: brooding; direct development; large eggs; mpa namuncura; burdwood bank; sub-antarctic waters; trochita pileolus